PENGARUH EMPLOYEE CREATIVITY TERHADAP JOB PERFORMANCE YANG DIMEDIASI OLEH JOB SATISFACTION PADA KARYAWAN XYZ HOSPITALITY KOTA BANDUNG - Jessica Claudia Kurniawan; Yohanes Arianto Budi Nugroho (Jurnal Manajemen, 2021)
The purpose of this study was to see the effect of employee creativity on job performance mediated by job satisfaction. This research was conducted at XYZ Hospitality Bandung City. Respondents in this study were 65 employees who worked in 5 (five) departments, namely Marketing & Sales, Personnel (Human Resource), Food & Beverage, Room Division, and Purchasing. The method used is Non-Probability / Non-Random Sampling. Data processing was performed using IBM SPSS Statistics 26 and Macro Hayes PROCESS software. The results of this study indicate that (1) employee creativity has a positive and significant effect on job satisfaction, (2) job satisfaction has no significant effect on job performance, (3) employee creativity has a positive and significant effect on job performance, and (4) employee creativity has no effect on job performance with job satisfaction as a mediating variable.